Advances in Human and Machine Navigation Systems - Róka, Rastislav (IntechOpen, 2019)
Advances in Human and Machine Navigation Systems provides a platform for practicing researchers, academics, PhD students, and other scientists to design, analyze, evaluate, process, and implement diversiform issues of navigation systems, including life-improving advances in human navigation systems and advances improving machine navigation systems. The five chapters of the book demonstrate the capabilities of navigation systems to solve scientific and engineering problems with varying degrees of complexity.